STUDY ON THE DEVELOPMENT AND GROWTH OF LARVES OF TIGER GROUPER Epinephelus fuscoguttatus (Forskal, 1775) AT DIFFERENT MEDIA TEMPERATURES - Virgia Wulandari; Indra Gumay Yudha; Eko Effendi (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2020)
Water temperature has an influence on the development and growth of fish larvae. The appropriate water temperature can caused the development and growth of fish larvae optimum. This research aimed to study the effect of water temperature on the development and growth of brown marbled grouper larvae. This experimental design used a completely randomized design that had 3 treatments (26-28°C, 28-30°C, 30-32°C) equipped with 3 replications each. The parameters observed were the duration of yolk absorption, morphogenesis of larvae, and growth of body length. Data of larval morphogenesis development were analyzed descriptively, while the duration of yolk absorption and larval growth were analyzed of variance and post hoc test using the Least Significant Difference (LSD). The results showed that water temperature influenced morphogenesis development, the duration of yolk absorption, and the growth of larval significantly different. The result showed, larvae had morphological development and duration of yolk absorption faster in warmer incubation media.